Design and fabrication of portable cloth rack / Nur Iman Ezani - Ezani, Nur Iman (2022)
Cloth rack is usually used to dry wet laundry by evaporation. The cloth rack is made of wood, metal or plastic. The problems that can be seen with the common design of cloth rack is that it is heavy and difficult to move. It also not ergonomic. This project goal is to redesign and create a portable cloth rack using SOLIDWORKS to CAD modelling the project to solve the problem revolves around current cloth rack design which is the difficulty to move the cloth rack around and takes up a lot of spaces. There are many process involved in fabricating the cloth rack such as welding, cutting and milling process. The suggested design for the cloth rack is by using hollow stainless steel pole as the main material, wheels and detachable sections. The expected result will be detachable cloth rack to comply with the objectives stated. As a conclusion, this project is to improve cloth rack design for better quality of life.